ANALISIS REAKSI PASAR TERHADAP PERISTIWA CUM DIVIDEND DATE PADA PERUSAHAAN PERBANKAN BERKAPITALISASI BESAR YANG TERDAFTAR DI BURSA EFEK INDONESIA (STUDI EVENT STUDY MENGGUNAKAN AVERAGE ABNORMAL RETURN DAN AVERAGE TRADING VOLUME ACTIVITY) - Inayah Chintaki MZ; Huriyn Putri Askiah Juhari; Irwan Pratama; Syamsuddin; Aini Indrijawati (STKIP Subang, 2026)
This study examines market reactions to the cum dividend date among large-cap banking companies listed on the Indonesia Stock Exchange using Average Abnormal Return (AAR) and Average Trading Volume Activity (ATVA) as indicators of market response. Employing a quantitative approach and an event study methodology, the research focuses on four major banking firms: PT Bank Central Asia Tbk (BBCA), PT Bank Rakyat Indonesia (Persero) Tbk (BBRI), PT Bank Mandiri (Persero) Tbk (BMRI), and PT Bank Negara Indonesia (Persero) Tbk (BBNI). The observation period covers five trading days before the event (Day −5 to Day 0) and five trading days after the event (Day +1 to Day +5). Data were collected from the Indonesia Stock Exchange and Yahoo Finance and analyzed using the Market-Adjusted Model with EViews software.The findings reveal no significant difference in AAR before and after the cum dividend date, with a probability value of 0.7842. Likewise, no significant difference is observed in ATVA, as indicated by a probability value of 0.6696. Although descriptive results show a decline in AAR on the cum dividend date and an increase in trading activity following the event, these changes are not sustained throughout the observation period. The results suggest that dividend-related information had been anticipated by investors before the cum dividend date, thereby limiting the market reaction to the event.